The Impact of Problem-Based Learning on Creative Thinking and Learning Motivation of Elementary School Students - Firawaty, Firawaty; Wijayanto, Zainnur; Nisa, Ana Fitrotun; Jarapa, Amelia A. (FKIP Universitas Lampung, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on elementary school students’ creative thinking skills and motivation to learn mathematics. The background of this research is based on findings from several elementary schools in Cluster 2 of Jatinom Subdistrict, which indicate low levels of learning motivation, creative thinking ability, and suboptimal mathematics learning outcomes. Low participation in discussions, difficulty solving word problems, and lower mathematics scores compared to other subjects are key indicators of the issue. This research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The population consisted of all fourth-grade students, totaling 224 students. The sample was drawn from four classes, two experimental and two control classes, using purposive cluster random sampling. Data were collected through tests, observations, and documentation. The research instruments were tested for content and construct validity, and their reliability was calculated using Cronbach’s Alpha. Data were analyzed using normality and homogeneity tests, as well as hypothesis testing through paired sample t-tests and independent sample t-tests using SPSS 30. The results showed that both the PBL model and the expository method had a positive impact on improving students’ creative thinking skills and learning motivation in mathematics. However, there was a significant difference between the two, with the PBL group consistently demonstrating higher improvement. The effectiveness of PBL is attributed to a learning process that actively engages students in contextual problem-solving, encourages collaboration, and fosters understanding through direct experience. Its emphasis on student-centered inquiry, deeper cognitive engagement, and active problem-solving likely contributes to its superior outcomes. Thus, PBL is proven to be more effective than the expository method in enhancing both aspects among elementary school students. Keywords: problem-based learning, creative thinking, learning motivation.